The Potential of GPT in Education: Opportunities for Students’ Feedback - Akhyar, Yundri; Ningsih, Wirda (Poltanesa, 2024)
The objective of this study is to investigate the capacity of GPT (Generative Pre-trained Transformer) in delivering feedback to students. The research methodology employed was bibliographic research, involving the gathering of data from various sources such as books, articles, and academic documents. The findings uncover various crucial prospects for employing GPT in providing feedback to students. Firstly, GPT has the ability to automate the generation of feedback, providing consistent and immediate responses. Additionally, it facilitates personalised learning by customising feedback to meet the specific needs of each student, enabling multiple instances of personalised learning reinforcement. In addition, GPT offers language assistance, aiding students in overcoming linguistic obstacles. It improves the process of creating content by aiding in the development of educational materials and assignments. Another notable benefit is its round-the-clock availability, guaranteeing that students can receive feedback at any hour, thereby enhancing their learning experience. Finally, GPT can be incorporated into cutting-edge educational applications, promoting a more interactive and captivating learning environment. In summary, GPT's ability to produce automated, tailored, and easily accessible feedback demonstrates its potential to greatly enhance educational methods and student achievements.